2018
DOI: 10.1002/chem.201800412
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Metallopolymer Design: Redox‐Controlled Surfaces, Porous Membranes, and Switchable Optical Materials Using Ferrocene‐Containing Polymers

Abstract: Metallopolymers with metal functionalities are a unique class of functional materials. Their redox-mediated optoelectronic and catalytic switching capabilities, their outstanding structure formation and separation capabilities have been reported recently. Within this Minireview, the scope and limitations of intriguing ferrocene-containing systems will be discussed. In the first section recent advances in metallopolymer design will be given leading to a plethora of novel metallopolymer architectures. Discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 137 publications
(331 reference statements)
0
54
0
Order By: Relevance
“…Metallopolymers are functional polymers with metal centers in their frameworks, which can integrate both the functions of metal elements and the properties of polymers . Many different metal‐containing building blocks and polymer topologies have been reported .…”
Section: Methodsmentioning
confidence: 99%
“…Metallopolymers are functional polymers with metal centers in their frameworks, which can integrate both the functions of metal elements and the properties of polymers . Many different metal‐containing building blocks and polymer topologies have been reported .…”
Section: Methodsmentioning
confidence: 99%
“…With this method, high‐fidelity colloid micropatterns can be formed in seconds. This work expands the utility of ferrocene‐based redox‐controlled surfaces, which was pioneered by the Whitesides group and has since then seen quite exciting new development in the field of metallopolymers …”
Section: Introductionmentioning
confidence: 78%
“…Elbert et al [41] reported that it is possible to reversibly modulate the catalytic activity of Grubbs Second Generation catalyst for the ROMP (ring-opening metathesis polymerization) reaction of nerbornene when it is immobilized on the surface of SiO 2 NPs functionalized with poly (vinylferrocene). In fact, when poly(vinylferrocene) is oxidized, it increases its hydrophilicity and the polymeric network swells [42] creating a thicker shell layer that hinders the diffusion of apolar molecules (such as nerbornene) toward the catalyst. As a consequence, after oxidation of the poly(vinylferrocene), the ROMP reaction can be not catalyzed by the immobilized Grubbs Second Generation catalysts, which are not accessible to norbonene monomers.…”
Section: Switchable Catalysis Based On Variation Of Ph Ionic Strengtmentioning
confidence: 99%